Key Strategies Predicting Industrial Participation in the Malaysian Apprenticeship Programme - Abdullah, Roziyati; Leman, Zulkiflle; Baharudin, B.T Hang Tuah; Ahmad, Siti Azfanizam (Journal of Technical Education and Training, 2025)
The National Dual Training System (NDTS), which is a Malaysian apprenticeship programme, is highlighted as the top national agenda in producing skilful workers for industrial requirements. Since 70% to 80% of apprentices’ practical training takes place in a real-world workplace, industries involvement are important to the programme's success. Nonetheless, the participation rate decreases over the years despite numerous incentives being provided. The current study aims to statistically investigate the most effective strategies for the government to increase industry participation in the NDTS, which was not explored by previous studies. Specifically, the relationship between the five strategies, namely financial incentives, digital administration, productive collaboration, flexible implementation, and efficient promotion on industry participation, was examined. A set of questionnaires was distributed to NDTS manufacturing companies, and the collected data were analysed via Partial Least Square-Structural Equation Modelling (PLS-SEM). The structural model relationship analysis revealed that only three strategies, namely financial incentives, flexible implementation, and efficient promotion, demonstrated significant, positive, and direct relationships with industry participation. Digital administration and productive collaboration required efficient promotion as the mediator to demonstrate indirect positive relationships with industry participation. Further analysis of Importance-Performance Analysis (IPMA) matrix corroborated that the government should focus on flexible implementation and efficient promotion through digital administration to enhance industrial participation in the NDTS. The current study provides a practical solution for the policymakers to improve efficiency in governmental decision-making and public-service delivery to improve industrial trust and confidence in governmental programmes. The present study could be expanded to improve delivery in other skill training programmes in future.